Invasive infections due to Saprochaete and Geotrichum species: Report of 23 cases from the FungiScope Registry. Issue 4 (2nd February 2017) - Durán Graeff, Luisa; Seidel, Danila; Vehreschild, Maria J. G. T.; Hamprecht, Axel; Kindo, Anupma; Racil, Zdenek; Demeter, Judit; De Hoog, Sybren; Aurbach, Ute; Ziegler, Maren; Wisplinghoff, Hilmar; Cornely, Oliver A.; et al.
Summary: Saprochaete and Geotrichum spp. are rare emerging fungi causing invasive fungal diseases in immunosuppressed patients and scarce evidence is available for treatment decisions. Among 505 cases of rare IFD from the FungiScope ™ registry, we identified 23 cases of invasive infections caused by these fungi reported from 10 countries over a 12‐year period. All cases were adults and previous chemotherapy with associated neutropenia was the most common co‐morbidity. Fungaemia was confirmed in 14 (61%) cases and deep organ involvement included lungs, liver, spleen, central nervous system and kidneys. Fungi were S. capitata (n=14), S. clavata (n=5), G. candidum (n=2) and Geotrichum spp. (n=2). Susceptibility was tested in 16 (70%) isolates. All S. capitata and S. clavata isolates with the exception of one S. capitata (MIC 4 mg/L) isolate had MICs>32 mg/L for caspofungin. For micafungin and anidulafungin, MICs varied between 0.25 and >32 mg/L. One case was diagnosed postmortem, 22 patients received targeted treatment, with voriconazole as the most frequent first line drug. Overall mortality was 65% (n=15). Initial echinocandin treatment was associated with worse outcome at day 30 when compared to treatment with other antifungals (amphotericin B ± flucytosine, voriconazole, fluconazole and itraconazole) ( P =.036). Echinocandins are not an option for these infections.